Analytical process and system design of integrated fault diagnostic system. (27th August 2009) - Gabbar, Hossam A.; Sayed, Hanaa E.; Osunleke, Ajiboye S.; Hara, Masanobu
There is an increasing interest to find an effective mechanism for fault diagnosis, which is essential for safe plant operation and optimised maintenance. This paper presents an integrated framework for qualitative and quantitative fault diagnosis mechanism where qualitative fault models are developed for the underlying plant process and equipment and linked with quantitative methods on the basis of trend analysis. The proposed fault diagnosis process is described using detailed activity models. The proposed integrated fault diagnosis framework is illustrated using a case study experimental plant G-Plant, which showed improved fault diagnosis capabilities in terms of root cause and consequence analysis.